Influence of phytophagous mammals environment-forming activity on the soil invertase fermentative activity in conditions of mining impact region - Kirienko, Svetlana; Didur, Oleg; Loza, Iryna; Pakhomov, Olexandr (Acta Agraria Debreceniensis, 2010)
Excretorial and fossorial activity of mammals is an important part of environment-forming activity. Mammals have influences on important biogeocenotic processes, especially on the soil processes. Determination the maintenance of soil invertase as one of diagnostic description the ecological state allowed defining limits of oscillation index in dump areas and in clean (control) native areas. The obtained results of the investigation indicate the soil depth, duration of experiment and type of area influence on soil invertase activity with the high statistical level of significance. Positive influence is revealed on invertase activity changing on dump areas, where an active excretorial and fossorial activity of phytophagous mammals was observed.